PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN: STUDI PADA GENERASI Z - Larasati, Dian Ayu; Siregar, Salim (An Nuqud Journal of Islamic Economics, 2025)
Social media has become an essential part of daily life, especially for Generation Z, who grew up alongside the advancement of digital technology. Platforms such as Instagram, TikTok, and YouTube not only serve as tools for communication and entertainment but also play a crucial role in influencing consumer purchasing decisions. Decisions that were once based on needs and logical considerations are now largely influenced by visual content, user reviews, and promotions carried out by influencers. This study aims to analyze the impact of social media on consumer purchasing decisions with a focus on Generation Z. The method used is a literature review of various scientific journals and relevant credible sources. The findings indicate that social media significantly affects every stage of the purchasing decision-making process, from information search and evaluation of alternatives to the act of purchasing. The study also reveals an increase in impulsive buying behavior triggered by product visualization and recommendations from digital figures. This article recommends enhancing digital and financial literacy among Generation Z to enable them to make wiser purchasing decisions based on thorough consideration.